Javni sektor in internet - Vintar, Mirko (Uporabna informatika (Ljubljana), 2000)
These days Internet is present at every step, mainly in the field of economy. Arrival in the public sector field is inevitable. In the paper we focused on central and local government bodies and their attitude towards information andcommunication technology. By analysing web pages, inquiring public servantsand testing the responses on citizens` questions we tried to discover influences of Internet on better informing of citizens, their participation inmaking decisions of public interest and communication between citizens and central and local government.
Keywords: internet; javni sektor; Slovenija